Desdobramentos das políticas públicas para as bibliotecas escolares em escolas do município de Araguaína/TO - Almeida, Núbia Régia de (2020)
The present research shows the results of public policies for school libraries related to the three governmental spheres. The field research focused on three schools in the municipality of Araguaína-TO, being one of the municipal network, another of the state and, the last of the federal one. To achieve that objective, it was sought to identify and to describe these policies within each one of the three areas; identify and describe the functioning of these public policies in the respective school libraries; as well as to ascertain if these libraries are fulfilling their pedagogical function aiming at the formation of the reader. This is study of case with a qualitative approach, involving bibliographical and documentary research, carried out through comparative analyzes of the school libraries pedagogical practices linked to the mentioned schools. As instruments and procedures for data generation, several documents were consulted and analyzed, such as the work plan of those in charge of the school libraries, actions contemplated in the Political pedagogical Project / PPP of schools, reports, photographs, books portraying information about the collections and loans; observations of the work done in each one of these school libraries during the second half of 2016, with the due registration in the field journal; application of semistructured interviews with the school librarians, with teachers, and with managers of the Municipal and State Teaching Departments. The generated data were examined in the light of what the public policy plans for school libraries, as well as ideas about their pedagogical role in the training of readers. In order to interpret those data, the work of authors such as Eliana Yunes (1984, 2009, 2012), Gilda Carvalho (2012), Rovilson Silva (2009), Magda Soares (1999), Gleide Pereira and Bernadete Campello), Antonio Adailton Silva (2015), among other authors who deal with issues related to school libraries and the training of readers were studied. It was verified there was an advance in Brazil from the year of 1990 on, in what concerns to the elaboration and approval of public policies for the school libraries. Among them, can be mentioned the creation of PNBE, currently attended by PNLD, approval of law 12.244, which deals with the popularization of school libraries, as well as actions directed at PNLL, PNE, PME, PEE. However, the legislation has not ensured the application of laws in libraries, the results pointed out that 97.46% of schools in the municipal network of Araguaína / TO do not have school libraries and in the state sphere, 29.32%. Also, it was verified that the investment in public policies directed to the formation of mediators of reading is insignificant, therefore, even in the schools that have BE, the effectiveness of these public policies made for them in order to their formation of readers is still insignificant in relation to its main expectation, which is, to make the library a reference space to collaborate in the formation of the reader, the development of its literacy and its autonomy to continue learning based on the knowledge built from the mediations carried out in the scope, also, of the school library .